Decreased proteinase A excretion by strengthening its vacuolar sorting and weakening its constitutive secretion in Saccharomyces cerevisiae. (1st January 2017) - Chen, Yefu; Song, Lulu; Han, Yueran; Liu, Mingming; Gong, Rui; Luo, Weiwei; Guo, Xuewu; Xiao, Dongguang
Abstract: Proteinase A (PrA), encoded by PEP4 gene, is detrimental to beer foam stability. There are two transport pathways for the new synthesized PrA in yeast, sorting to the vacuole normally, or excreting out of the cells under stress conditions. They were designated as the Golgi-to-vacuole pathway and the constitutive secretory pathway, respectively. To reduce PrA excretion in some new way instead of its coding gene deletion, which had a negative effect on cell metabolism and beer fermentation, we modified the PrA transport based on these above two pathways. In the Golgi-to-vacuole pathway, after the verification that Vps10p is the dominant sorting receptor for PrA Golgi-to-vacuolar transportation by VPS10 deletion, VPS10 was then overexpressed. Furthermore, S EC5, encoding exocyst complexes' central subunit (Sec5p) in the constitutive secretory pathway, was deleted. The results show that PrA activity in the broth fermented with WGV10 ( VPS10 overexpressing strain) and W∆SEC5 ( SEC5 deletion strain) was lowered by 76.96 and 32.39%, compared with the parental strain W303-1A, at the end of main fermentation. There are negligible changes in fermentation performance between W∆SEC5 and W303-1A, whereas, surprisingly, WGV10 had a significantly improved fermentation performance compared with W303-1A. WGV10 has an increased growth rate, resulting in higher biomass and faster fermentation speed; finally, wort fermentation is performed thoroughly. The results show that the biomass production of WGV10 is always higher than that of W∆SEC5 and W303-1A at all stages of fermentation, and that ethanol production of WGV10 is 1.41-fold higher than that of W303-1A. Obviously, VPS10 overexpression is beneficial for yeast and is a more promising method for reduction of PrA excretion.